2003
DOI: 10.1034/j.1600-0706.2003.12178.x
|View full text |Cite
|
Sign up to set email alerts
|

Environmental heterogeneity and the evolution of foraging behaviour in long ranging greater albatrosses

Abstract: Habitat selection in heterogeneous environments is assumed to allow diversification. Wide‐ranging species like pelagic seabirds present a paradox, in that their diversity appears difficult to reconcile with a frequent lack of geographical isolation between populations. We studied the foraging strategies of three closely related species of greater albatrosses, wandering albatross, Diomedea exulans, Amsterdam albatrosses D. amsterdamensis and royal albatross, D. epomophora, in relation to environmental heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 28 publications
1
43
1
Order By: Relevance
“…Similarly, in a recent interspecific comparison of variation in habitat preferences of great albatrosses (Diomedea spp. ), Waugh & Weimerskirch (2003) suggested that the longer wings relative to body mass of Amsterdam albatrosses facilitated their foraging in tropical waters.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a recent interspecific comparison of variation in habitat preferences of great albatrosses (Diomedea spp. ), Waugh & Weimerskirch (2003) suggested that the longer wings relative to body mass of Amsterdam albatrosses facilitated their foraging in tropical waters.…”
Section: Discussionmentioning
confidence: 99%
“…At-sea distribution and movements of the Amsterdam albatross were previously largely unknown (see fragmented information on adults in Inchausti & Weimerskirch 2001, Waugh & Weimerskirch 2003, Rivalan et al 2010. Notably, both the apparent similarity of these birds with juvenile or immature birds of the more abundant wandering albatrosses and the extremely reduced population numbers precluded reliable ship-based surveys of their distribution (Roux et al 1983, Weimerskirch et al 1997).…”
Section: Variability In Distribution and Movementsmentioning
confidence: 99%
“…Our survey aims to identify which countries share responsibility for the species' conservation at sea, where it is legally feasible to engage efforts. Little information was previously available on this species' distribution during breeding (Waugh & Weimerskirch 2003), and thanks to the tremendous development of telemetric approaches (Wilson & Vandenabeele 2012), we have been able to compile a unique data set of individual tracking records on all age-(juvenile, immature, adult) and breeding-related (incubation, brooding, chick-rearing, sabbatical, failed breeder) classes of the population, including prolonged phases the birds spend exclusively at sea (Weimerskirch & Wilson 2000, Weimerskirch et al 2006. Our study provides (1) one of the first tracking surveys of an albatross species covering its entire life cycle (see also Weimerskirch et al 2014), and (2) the scientific basis for the implementation of conservation measures within EEZs.…”
Section: Introductionmentioning
confidence: 99%
“…During the breeding season, adults are amenable to the short-term deployment and retrieval of devices such as satellite transmitters and Global Positioning System (GPS) loggers, and the burgeoning of studies since the early 1990s has provided unprecedented opportunities to investigate the complex variation within and between species in at-sea distributions (Hyrenbach et al 2002, Waugh & Weimerskirch 2003, Phillips et al 2005a). These suggest a number of mechanisms that may reduce the level of inter-specific competition for resources, including spatial, dietary and behavioural segregation at sea, and to a lesser extent differences in timing of breeding and hence peak demand for prey.…”
Section: Introductionmentioning
confidence: 99%